Depot Sanitation, Hygiene, and Analysis of Total Microba Control in Refilled Drinking Water in The Barus District - Nurhanifah Siregar; Wiwi Wardani Tanjung; Lena Juliana Harahap (International Journal of Basic and Applied Science, 2022)
Water is the most important requirement for life. People would prefer to refill their drinking water to satisfy their needs because it is easier and more efficient. It is important to implement hygiene and sanitation measures at drinking water depots if the drinking water produced is to be healthy and safe. Contamination of water can occur if drinking water depots are not kept clean and sanitary. The research used is a descriptive study conducted in the Barus District, with the goal of providing a description of the depot's hygiene and sanitation, as well as laboratory analysis to identify the total contamination of coliform bacteria in the Barus District's Refill Drinking Water Depot. According to the Minister of Health of the Republic of Indonesia no 43 in 2014. None of the drinking water depots in Barus district met the physical qualifying requirements. The exam resulted in a score of 70 or higher. and the results of laboratory tests on the bacteriological quality of drinking water replenished with all coliform-contaminated drinking water samples that exceeded the quality satandard. As a result, the depot owner should turn on the disinfection equipment when starting work and always pay attention to building sanitation, employee hygiene and maintaining drinking water treatment equipment to prevent contamination of drinking water.